The representation of kingship and co-rulership in the Norwegian Kings' Sagas, c.1030-c.1130. - Clark, Harriet (2024)
This thesis addresses the question of how the respective authors of Ágrip af Nóregskonunga sǫgum, Morkinskinna, Fagrskinna, and Heimskringla depicted the ideal qualities for kingship in the cases of co-kings in the period c.1030–c.1130. Previous research into kingship ideology has largely focused on a normative model of singular monarchy, with co-kingship typically seen as either a sign of an unstable political system, or that the tensions which formed between co-kings ensured a stable society. Both of these views rest on the assumption that co-kings were inherent rivals, and that they are depicted as such in the Norwegian kings’ sagas. The present study challenges this assumption, and demonstrates how the authors of Ágrip, Morkinskinna, Fagrskinna, and Heimskringla depicted co-kings as complementary and collaborative units of ideal kingship.